Reconciling the differences in aggregate U.S. wage series - Julien Champagne; André Kurmann; Jay Stewart (Bank of Canada, 2016)
Average hourly real wage series from the Labor Productivity and Costs (LPC) program and the Current Employment Statistics (CES) program have evolved very differently over the past decades. While the LPC wage has grown consistently over time and become markedly more volatile since the mid-1980s, the CES wage stagnated from the early 1970s to the mid-1990s and experienced a substantial drop in volatility since the mid- 1980s. These differences are due to the divergent evolution of average weekly earnings in the two data sets. Average weekly hours, by contrast, have evolved very similarly. Using information from the Current Population Survey and other publicly available data, we identify two principal sources for the divergent evolution of weekly earnings: differences in earnings concept (employer-paid supplements and irregular earnings of high-income individuals included in the LPC data but not in the CES data); and differences in worker coverage (all non-farm business workers for the LPC data versus production and nonsupervisory workers in private non-agricultural establishments for the CES data). The results have important implications for the appropriate choice of aggregate wage series in macroeconomic applications.
Keywords: E01; E24; E30; J30; 330; Business fluctuations and cycles; Labour markets